Experimental and phenomenological investigations of diffusion in Co–Al–W alloys. (September 2015) - Chang, Hui; Xu, Guanglong; Lu, Xiao-Gang; Zhou, Lian; Ishida, Kiyohito; Cui, Yuwen
Highlights: Error function expansion (ERFEX) was used to represent diffusion-couple profiles. ERFEX allows acquisition of inter/impurity diffusion coefficients of Co–Al–W alloys. The mobility has proven ability to predict diffusion details in Co–Al–W alloys. Abstract : Diffusion coefficients of the fcc Co–Al–W alloys were extracted from extensive diffusion couple experiments performed at 1173–1573 K, which were afterwards assessed to develop their diffusion mobility in the context of phenomenological treatment. We demonstrate that the mobility enables the prediction of diffusion picture of technologically important Co–Al–W alloys.